Pelatihan Pengelolaan Sumber Daya untuk Pendidikan Anak Berkebutuhan Khusus pada Lembaga KAZAMA - Asep Dony; Aprilia Puspasari; Irwan Raharja; Popon Rabia Adawia (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
This community service activity aims to improve the competence of parents and managers of children with special needs resources in providing education effectively and sustainably. This training was motivated by the still low understanding of institutional managers regarding school resource management, especially in the aspects of planning, utilization, and evaluation of human resources and infrastructure. The activity was carried out on Sunday, October 19, 2025, through the stages of opening, delivery of materials, interactive discussion sessions, filling out questionnaires, and closing. The implementation method involved a participatory approach so that participants could play an active role in the learning process. The implementation of the community service took place in a special room of the Lazama institution. It was attended by approximately 20 participants consisting of special needs school management and parents. The results of the activity showed that participants experienced significant improvements in their understanding of concepts and practical skills in school resource management. Ninety-two percent of participants stated that the training material was highly relevant, 88% stated that their understanding improved, and 85% stated that they were ready to implement the strategies they had learned. The training also encouraged the formation of an internal resource management team at the KAZAMA Institute as a follow-up to the program. This activity not only increased the individual capacity of participants but also strengthened sustainable institutional governance. This community service activity successfully raised new awareness about the importance of collaborative, adaptive, and sustainability-oriented educational resource management, particularly in schools serving children with special needs.